Portopulmonary hypertension in decompensated cirrhosis with refractory ascites. Issue 9 (11th August 2003) - Benjaminov, F S; Prentice, M; Sniderman, K W; Siu, S; Liu, P; Wong, F
Abstract : Background: The prevalence of portopulmonary hypertension (PPHTN) in patients with cirrhosis and refractory ascites is unknown. Its presence may preclude patients from receiving a transjugular intrahepatic portosystemic shunt or liver transplantation as a definitive treatment for their end stage cirrhosis. Purpose: To determine the prevalence, possible aetiological factors, and predictive factors for the development of PPHTN in these patients. Methods: Sixty two patients (53 males, nine females; mean age 54.5 (1.4) years) with biopsy proven cirrhosis and refractory ascites underwent angiographic measurements of pulmonary and splanchnic haemodynamics. Endothelin 1 levels were measured from the pulmonary artery. Forty nine patients underwent radionuclide angiography for measurements of central blood volume, pulmonary vascular, and cardiac chamber volumes. Forty seven patients also underwent two dimensional echocardiography for measurements of cardiac structural and functional parameters. Cardiac output, and systemic and pulmonary vascular resistance were calculated. Results: Ten patients (16.1%) fulfilled the criteria for PPHTN (mean pulmonary artery pressure ≥25 mm Hg and pulmonary vascular resistance ≥120 dyn×s/cm 5 ), with significantly higher mean right atrial (15.4 (1.2) v 7.9 (0.5) mm Hg; p<0.001), and right ventricular pressures (24.7 (1.5) v 14.7 (0.6) mm Hg; p<0.001), and endothelin 1 levels (3.04 (0.40) v 1.98 (0.12) pg/ml; p=0.02). No significant differences in any of the other parameters measured were detected between the two groups. A right atrial pressure of ≥14 mm Hg had a 83% positive predictive value for the presence of PPHTN. Conclusions: Portopulmonary hypertension is common in cirrhosis with refractory ascites, possibly due to excess endothelin 1 in the pulmonary circulation. An elevated right atrial pressure ≥14 mm Hg predicts the presence of PPHTN, which may be helpful in deciding management options in these patients.